Human Integration of a Character-based Curriculum and Humanistic Values As Basic Initiation of a Human Rights-friendly School - Wahjusaputri, S (KnE Social Sciences, 2018)
A Human Rights-Friendly School is founded where human rights are learned, taught, practiced, respected, protected, and promoted. A qualitative approach was taken and the study used thematic analysis of key concepts and codes. The study aims to build the capacity of the whole school community by promoting a democratic environment, innovative teaching methods, and responsible citizenship. From the way decisions are made in schools, to the way people treat each other, to the curriculum and extracurricular activities on offer, right down to the very surroundings in which students are taught, the school becomes an exemplary model for human rights education. Keywords: character-based curriculum, humanistic values, human rights-friendly school